Nickel(ii) complexes based on dithiolate–polyamine binary ligand systems: crystal structures, hirshfeld surface analysis, theoretical study, and catalytic activity study on photocatalytic hydrogen generation. Issue 16 (12th April 2021) - Adhikari, Suman; Bhattacharjee, Tirtha; Bhattacharjee, Sharmila; Daniliuc, Constantin Gabriel; Frontera, Antonio; Lopato, Eric M.; Bernhard, Stefan
Abstract : To ascertain the influence of binary ligand systems on the coordination modes of the Ni(ii ) metal center and resulting supramolecular architectures, three Ni(ii ) thiolate complexes have been synthesized in high yield in one step in water and structurally characterized. Abstract : To ascertain the influence of binary ligand systems [1, 1-dicyanoethylene-2, 2-dithiolate (i-mnt −2 ) and polyamine tetraen = tris(2-aminoethyl)amine, tren = diethylene triamine and opda = o -phenylenediamine] on the coordination modes of the Ni(ii ) metal center and resulting supramolecular architectures, a series of nickel(ii ) thiolate complexes [Ni(tetraen)(i-mnt)](DMSO) (1 ), [Ni2 (tren)2 (i-mnt)2 ] (2 ), and [Ni2 (i-mnt)2 (opda)2 ] n (3 ) have been synthesized in high yield in one step in water and structurally characterized by single crystal X-ray crystallography and spectroscopic techniques. X-ray diffraction studies disclose the diverse i-mnt −2 coordination to the Ni +2 center in the presence of active polyamine ligands, forming a slightly distorted octahedral geometry (NiN4 S2 ) in 1, square planar (NiS4 ) and distorted octahedral geometries (NiN6 ) in the bimetallic co-crystallized aggregate of cationic [Ni(tren)2 ] +2 and anionic [Ni(i-mnt)2 ] −2 in 2, and a one dimensional (1D) polymeric chain along the [100] axis in 3, having consecutive square planar (NiS4 ) and octahedral (NiN6 ) coordination kernels. The N–H⋯O, N–H⋯S, N–H⋯N, N–H⋯S, N–H⋯N, and N–H⋯O type hydrogen bonds stabilize the supramolecular assemblies in 1, 2, and 3 respectively imparting interesting graph-set-motifs. The molecular Hirshfeld surface analyses (HS) and 2D fingerprint plots were utilized for decoding all types of non-covalent contacts in the crystal networks. Atomic HS analysis of the Ni +2 centers reveals significant Ni–N metal–ligand interactions compared to Ni–S interactions. We have also studied the unorthodox interactions observed in the solid state structures of 1–3 by QTAIM and NBO analyses. Moreover, all the complexes proved to be highly active water reduction co-catalysts (WRC) in a photo-catalytic hydrogen evolution process involving iridium photosensitizers, wherein 2 and 3 having a square planar arrangement around the nickel center(s) – were found to be the most active ones, achieving 1000 and 1119 turnover numbers (TON), respectively.